Modulation of Peripheral CD4+CD25+Foxp3+ Regulatory T Cells Ameliorates Surgical Stress-Induced Atherosclerotic Plaque Progression in ApoE-Deficient Mice - Handke, Jessica; Kummer, Laura; Weigand, Markus A.; Larmann, Jan (Frontiers in Cardiovascular Medicine, 2021)
Systemic inflammation associated with major surgery rapidly accelerates atherosclerotic plaque progression in mice. Regulatory T cells (Tregs) have emerged as important modulators of atherogenesis. In coronary artery disease patients, low frequency of Tregs constitutes an independent risk factor for cardiovascular complications after non-cardiac surgery. In this exploratory analysis, we investigate whether preoperative Treg levels affect surgery-induced atherosclerotic lesion destabilization in a murine model of perioperative stress. After nine weeks of high-cholesterol diet, atherosclerotic apolipoprotein E-deficient mice with modulated Treg levels were subjected to a 30-minute surgical procedure consisting of general isoflurane anesthesia, laparotomy and moderate blood loss. Controls underwent general anesthesia only. Brachiocephalic arteries were harvested three days after the intervention for histomorphological analyses of atherosclerotic plaques. Tregs were depleted by a single dose of anti-CD25 monoclonal antibody (mAb) administered six days prior to the intervention. Expansion of Tregs was induced by daily injections of IL-2/anti-IL-2 complex (IL-2C) on three consecutive days starting three days before surgery. Isotype-matched antibodies and PBS served as controls. Antibody-mediated modulation was Treg-specific. IL-2C treatment resulted in an eight-fold elevation of peripheral CD4+CD25+Foxp3+ Tregs compared to mice administered with anti-CD25 mAb. In mice treated with PBS and anti-CD25 mAb, surgical stress response caused a significant increase of atherosclerotic plaque necrosis (PBS: p < 0.001; anti-CD25 mAb: p = 0.037). Preoperative Treg expansion abrogated perioperative necrotic core formation (p = 0.556) and significantly enhanced postoperative atherosclerotic plaque stability compared to PBS-treated mice (p = 0.036). Postoperative plaque volume (p = 0.960), stenosis (p = 0.693), lesional collagen (p = 0.258), as well as the relative macrophage (p = 0.625) and smooth muscle cell content (p = 0.178) remained largely unaffected by preoperative Treg levels. In atherosclerotic mice, therapeutic expansion of Tregs prior to major surgery mitigates rapid effects on perioperative stress-driven atherosclerotic plaque destabilization. Future studies will show, whether short-term interventions modulating perioperative inflammation qualify for prevention of cardiovascular events associated with major non-cardiac surgery.